Passiflora nitida Kunth fruit: Chemical analysis, antioxidant capacity, and cytotoxicity - PEREIRA, Zilanir Carvalho; CRUZ, Josias Martins dos Anjos; CASTRO, Débora Raquel Gomes; RAMOS, Andrezza Silva; ROCHA, Daniel de Queiroz; ARRUDA, Henrique Silvano; BORSOI, Felipe Tecchio; NERI-NUMA, Iramaia Angelica; PASTORE, Glaucia Maria; SANCHES, Edgar Aparecido; CAMPELO, Pedro Henrique; FARIA, Jerusa Araújo Quintão Arantes; et al. (Food Science and Technology, 2024)
Passiflora nitida is a fruit-bearing species native to the Amazon region, considered an unconventional food plant, with its fruit commonly known as wild passion fruit. The aim of this study was to investigate the antioxidant properties, chemical profile, phenolic composition, and cytotoxicity of pulps and teas based on the pulp of P. nitida, contributing to the exploration of this species. This study provides important information about the chemical composition, which will contribute to the development of products based on wild passion fruit. The production of nonalcoholic beverages from the pulp with seeds is a viable alternative for utilizing the fruits with greater results, potentially offering a product with higher bioactive compounds and antioxidant capacity compared to seedless pulp. Moreover, P. nitida seed tea may constitute a significant source of nutrients for human consumption.